Evaluation of the Regional Choice Initiative - Phillips, Andrea (RAND Corporation, 2016)
This evaluation describes the Regional Choice Initiative (RCI), a large-scale initiative in 17 school districts in Pennsylvania. The RCI sought to expand school choice and offer more-rigorous courses for students in grades 7 to 12. RAND evaluated the performance of the individual programs and the RCI overall. The authors also identified aspects of implementation that facilitated or hindered the performance of the RCI.